2017
DOI: 10.1007/s00168-017-0852-3
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between regional public and private investment: evidence from Japanese prefectures

Abstract: This study examines the effects of government investment on private capital formation, considering both regional and sectoral distinctions in Japan. The empirical results show that a crowding-out effect is observed in rural areas for several industries that contribute to regional economic growth. This suggests that the allocation of public stimulus investment packages to stagnant regions in Japan might act as a regional growth constraint as well as an obstacle to the capital formation, and stagnant regions can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Based on Chen and Hwang, these linguistic variables can be converted into positive triangular fuzzy numbers [42]. The number of TFN is identified by (r, s, t) where r ≤ s ≤ t. Meanwhile, r = s = t is considered non-fuzzy, so the AHP scale converted to TFN can be made into PCM.…”
Section: F-ahpmentioning
confidence: 99%
“…Based on Chen and Hwang, these linguistic variables can be converted into positive triangular fuzzy numbers [42]. The number of TFN is identified by (r, s, t) where r ≤ s ≤ t. Meanwhile, r = s = t is considered non-fuzzy, so the AHP scale converted to TFN can be made into PCM.…”
Section: F-ahpmentioning
confidence: 99%
“…The nature and strength of the impact of budget expenditures on quantitative and qualitative parameters of socio-economic development remain the subject of discussion in Russian and foreign science (Andreyev & Polbin, 2018;Belyakov, 2018;Kudrin & Knobel, 2017;Gonzales-Paramo & Martinez, 2003;Miyazaki, 2018). The review of the research results related to this scientific problem revealed several approaches to the analysis (Andreyev & Polbin, 2018;Belyakov, 2018;Kudrin & Knobel, 2017;Zyablitskiy, 2018).…”
Section: Problem Statementmentioning
confidence: 99%
“…The issues of budget investments impact on the dynamics of economic development are more disclosed in foreign than in Russian scientific literature (Gonzales-Paramo & Martinez, 2003;Miyazaki, 2018). At the same time, in recent years there has been a steady increase in interest in this issue in Russian science.…”
Section: Problem Statementmentioning
confidence: 99%
“…Interestingly, they show that central government-financed investment spending has small multipliers ( » .4). 9 In a complementary study, Miyazaki (2018) shows large crowding-out effects of public spending on private investment in Japan, a result analogous to Cohen, Coval, and Malloy (2011).…”
Section: Introductionmentioning
confidence: 97%